An annotated checklist of the chewing lice (Phthiraptera: Ischnocera, Amblycera, Rhynchophthirina) from domestic and wild mammals in Malaysia - Kazim, Abdul-Rahman; Houssaini, Jamal; Tappe, Dennis; Heo, Chong-Chin (Zootaxa, 2023)
Literature records of chewing lice (Phthiraptera) from mammals in Malaysia were checked and reviewed, resulting in a list of 13 confirmed species belonging to eight genera (Bovicola, Felicola, Gliricola, Gyropus, Haematomyzus, Heterodoxus, Lorisicola, Trichodectes) from four families (Boopiidae, Gyropidae, Haematomyzidae, Trichodectidae) in three suborders (Amblycera, Ischnocera, Rhynchophthirina). We present a checklist of those 13 chewing lice recorded from Peninsular Malaysia and Malaysian Borneo, including hosts, localities, and literature references. An additional 12 species are listed and discussed as possibly occurring in this country. A host-louse list is also given.